Construccion de un mapa de ligamiento genetico preliminar en Coffea liberica x C. eugenioides - Lopez G, G.=700 1 Moncada B, M. del P.
(En, Es)
Ilus., 8 ref.
Keywords: CAFE; MAPAS GENETICOS; GENOMAS; COLOMBIA; LIGAMIENTO GENETICO; COFFEA LIBERICA; COFFEA EUGENIOIDES